Dispersal ability determines the role of environmental, spatial and temporal drivers of metacommunity structure. - André A Padial; Fernanda Ceschin; Steven A J Declerck; Luc De Meester; Cláudia C Bonecker; Fabio A Lansac-Tôha; Liliana Rodrigues; Luzia C Rodrigues; Sueli Train; Luiz F M Velho; Luis M Bini (PLoS ONE, 2014)
Recently, community ecologists are focusing on the relative importance of local environmental factors and proxies to dispersal limitation to explain spatial variation in community structure. Albeit less explored, temporal processes may also be important in explaining species composition variation in metacommunities occupying dynamic systems. We aimed to evaluate the relative role of environmental, spatial and temporal variables on the metacommunity structure of different organism groups in the Upper Paraná River floodplain (Brazil). We used data on macrophytes, fish, benthic macroinvertebrates, zooplankton, periphyton, and phytoplankton collected in up to 36 habitats during a total of eight sampling campaigns over two years. According to variation partitioning results, the importance of predictors varied among biological groups. Spatial predictors were particularly important for organisms with comparatively lower dispersal ability, such as aquatic macrophytes and fish. On the other hand, environmental predictors were particularly important for organisms with high dispersal ability, such as microalgae, indicating the importance of species sorting processes in shaping the community structure of these organisms. The importance of watercourse distances increased when spatial variables were the main predictors of metacommunity structure. The contribution of temporal predictors was low. Our results emphasize the strength of a trait-based analysis and of better defining spatial variables. More importantly, they supported the view that "all-or-nothing" interpretations on the mechanisms structuring metacommunities are rather the exception than the rule.